Preventing child sexual abuse : sharing the responsibility - Wurtele, Sandy K. (Sandy Kay), 1955- (Child, youth, and family services., 1992)
The past decade has seen a dramatic increase in the attention paid to the problem of child sexual abuse. Professionals from the social work, mental health, medical, academic, and legal fields are all involved in researching the prevalence, causes, and consequences of abuse. Child sexual abuse in multidimensional: it is determined by forces at work in victims and offenders, in the family, and in the community and society at large. Thoroughly researched, Preventing Child Sexual Abuse surveys incidence and prevalence studies; lists risk and protective factors in abuse; discusses various indicators of abuse; and reports on legislation related to abuse. It reviews preventive programs aimed at children and adults, and provides suggestions for an expanded involvement of parents, professionals, policymakers, researchers, and the general public. In doing so, it provides the information needed to create prevention programs that attack the problem on several fronts at o.